LAS LEYES DEL EMPERADOR HONORIO(395-423 d.C.): MISTICISMO Y ORATORIA. LA MAGIA DE LA PALABRA ESCRITA - Jordán Montés, J. F. (Antigüedad y Cristianismo, 1995)
In this article I intend to demonstrate, using a selection of laws, the philosophy and the mysticism of the Emperor in certain circumstances that took place in the period which coincides with the crises of the Roman State at the beginning of the fifth century A.C. The laws in the C. Th. and the information which they provide, are complemented by the data obtained from the historical sources of the epoch. At the same time a growing mysticism can be observed in the imperial legislation, an obsesion for the unity and a fear of the Final Judgement of God. History is converted into the reflection of the Divine Providence. (...)